Many hops, many stops: care-seeking “loops” for diabetes and hypertension in three urban informal settlements in the Mumbai Metropolitan Region - Ramani, Sudha; Bahuguna, Manjula; Spencer, Jennifer; Pathak, Sweety; Shende, Sushma; Pantvaidya, Shanti; D’Souza, Vanessa; Jayaraman, Anuja (Frontiers in Public Health, 2024)
Background: The burden of Non-Communicable Diseases (NCDs) in urban informal settlements across Lower and Middle Income Countries is increasing. In recognition, there has been interest in fine-tuning policies on NCDs to meet the unique needs of people living in these settlements. To inform such policy efforts, we studied the care-seeking journeys of people living in urban informal settlements for two NCDs- diabetes and hypertension. The study was done in the Mumbai Metropolitan Region, India. Methods: This qualitative study was based on interviews with patients having diabetes and hypertension, supplemented by interactions with the general community, private doctors, and public sector staff. We conducted a total of 47 interviews and 6 Focus Group Discussions. We synthesized data thematically and used the qualitative software NVivo Version 10.3 to aid the process. In this paper, we report on themes that we, as a team, interpreted as striking and policy-relevant features of peoples’ journeys. Results: People recounted having long and convoluted care-seeking journeys for the two NCDs we studied. There were several delays in diagnosis and treatment initiation. Most people’s first point of contact for medical care were local physicians with a non-allopathic degree, who were not always able to diagnose the two NCDs. People reported seeking care from a multitude of healthcare providers (public and private), and repeatedly switched providers. Their stories often comprised multiple points of diagnosis, re-diagnosis, treatment initiation, and treatment adjustments. Advice from neighbours, friends, and family played an essential role in shaping the care-seeking process. Trade-offs between saving costs and obtaining relief from symptoms were made constantly. Conclusions: Our paper attempts to bring the voices of people to the forefront of policies on NCDs. People’s convoluted journeys with numerous switches between providers indicate the need for trusted ‘first-contact’ points for NCD care. Integrating care across providers- public and private- in urban informal settlements – can go a long way in streamlining the NCD care-seeking process and making care more affordable for people. Educating the community on NCD prevention, screening, and treatment adherence; and establishing local support mechanisms (such as patient groups) may also help optimise people’s care-seeking pathways.